2008
DOI: 10.1161/circresaha.108.171488
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells and Transplant Arteriosclerosis

Abstract: Abstract-Stem

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 130 publications
0
54
0
1
Order By: Relevance
“…These SMCs then participate in the formation of neointima by decreasing the expression of SMC differentiation markers (1). Similarly, during the progression of atherosclerosis, recruited SMCs also acquired a transition to a synthetic phenotype in lesion formation (30). Studies on the mechanism of SMC de/differentiation are not only crucial for exploring human pathologies but are also useful for isolating and differentiating stem cells or vascular progenitors to SMCs, which is required for the tissue-engineered vessel.…”
Section: Discussionmentioning
confidence: 99%
“…These SMCs then participate in the formation of neointima by decreasing the expression of SMC differentiation markers (1). Similarly, during the progression of atherosclerosis, recruited SMCs also acquired a transition to a synthetic phenotype in lesion formation (30). Studies on the mechanism of SMC de/differentiation are not only crucial for exploring human pathologies but are also useful for isolating and differentiating stem cells or vascular progenitors to SMCs, which is required for the tissue-engineered vessel.…”
Section: Discussionmentioning
confidence: 99%
“…In their 2001 article using the same transplantation model, using ␤-galactosidase-Tg mice, Shimizu et al reported that neointimal SMCs were derived from the recipient BM cells rather than those of the donor, 5 a conclusion that has since been reached by others working in different models of IH. 31 These findings have remained controversial, in part because of the disputed ability of BM-derived cells to give rise to SMCs and because recent publications have directly contradicted the earlier data. 32,33 Recently, Iwata et al, working in 3 separate models of IH including TA, reported significant numbers of recipient ␣-SMA ϩ SM22␣ ϩ cells in the neointima, but these also expressed CD115, CD11b, F4/80, and Ly-6C, markers of the monocyte/macrophage lineage rather than established markers of differentiated SMCs such as smooth muscle myosin heavy chain or calponin.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, accumulating data indicate that non-bone marrow stem/progenitor cells contribute to repair damaged endothelial cells in several animal models. 9,11,35 Thus, endothelial regeneration in apoE Ϫ/Ϫ mice by stem cells should be higher if non-bone marrow-derived stem cells are taken into account.…”
Section: Stem Cells Contribute To Endothelial Repairmentioning
confidence: 99%